KEHIDUPAN NELAYAN SUMATERA BARAT DALAM KARYA GRAFIS - ZATUL HELMI, Yofita Sandra, S.Pd., M.Pd., Drs. Irwan, M.Sn. (Serupa The Journal of Art Education, 2016)
The creation of this final work aims to visualize the life of the fishermen of West Sumatra in the works of graphic art. Part of life that the author wants to interpretedis about the poverty of fishermen. The technique used is relief print with the type of linoleum cut. Relief Print is a technique in which the surface lines or fields to be printed is higher than the surface of the cliché. Higher surface that receives the ink and then applied to the paper . Through relief technique with the type of linoleum cut print, the author produced ten graphic artwork with the title : Mengais Rezeki, Terbiasa, Tak Dihiraukan, Waktu Senggang, 1:10, Para Penakhluk, Tua, Maelo Pukek, Pulang Malang, and Harapan. Each work interconection each other and have a similar theme, ideas and concepts.keywords: Fishermen, High Print Technique (relief print), linoleum cut.